Harvesting epithelial cell sheet based on thermo- sensitive hydrogel - Biazar, Esmaeil; Montazeri, Naser; Pourshamsian, Khalil; Asadifard, Farahnaz; Ghorbanalinezhad, Essmaeil; Heidari Keshel, Saeed; Hashemi, Mehrdad; Rahbar F.H, Sasan; Majdi, Ali (Archives of Advances in Biosciences, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} @font-face {font-family:"MS PGothic"; panose-1:2 11 6 0 7 2 5 8 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610612033 1757936891 16 0 131231 0;} @font-face {font-family:"\@MS PGothic"; panose-1:2 11 6 0 7 2 5 8 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610612033 1757936891 16 0 131231 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0in; margin-right:0in; margin-bottom:10.0pt; margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:Calibri; mso-bidi-font-family:Arial;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri; mso-bidi-font-family:Arial;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->Thermo-sensitive hydrogels were prepared by graft copolymerization of chitosan and N-Isopropylacrylamide via gamma radiation. Characterization of hydrogels such as 13C-NMR, DSC analysis and swelling test and cell assessments for harvesting living cell sheet were investigated. 13C-NMR and DSC analysis showed chitosan and NIPAAm monomer were grafted via gamma radiation successfully. Swelling ratio and curves results administrated hydrophilicity / hydrophobicity of hydrogel that this property is due to presence of PNIPAAm in different temperatures. The hydrogel was tested for harvesting epithelial cells after carrying out cell culture at 37 °C and incubating the confluent cells at 4°C for spontaneous detachment of cell sheet from hydrogel surface without enzyme treatment. Cell viability assay results and microscopic observations demonstrated that cells could attach to the hydrogel surface and maintain high viability and proliferation ability. Cell detachment efficiency from the hydrogel was high. These unique properties of the hydrogel would make it a promising support for epithelial cell grafting especially cornea regeneration.